Analysis of Design Changes from Main Engine Diesel Engine to Electric Engine on Fishing Vessels - Ramadhani, Dimitry Rizal; Pranatal, Erifive (Journal of Applied Sciences, Management and Engineering Technology, 2024)
Fishing vessels in Indonesia conventionally use diesel engines as their main propulsion engine. However, the use of diesel engines has quite a bad impact on the surrounding environment. So the latest innovations using alternative energy are needed. One of them is the use of electric engines as a replacement for diesel engines in the ship's main propulsion engine. The use of this electric machine will have a friendly impact on the environment. Apart from that, you don't need to spend a lot of money to maintain this electric machine. We can see this by comparing the ship's thrust requirements with maximum speed.